Work Cultural Values of Employees in the Postgraduate Environment of UIN Raden Intan Lampung - Erni Zuliana (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2026)
Abstract Higher education plays an important role in shaping the quality of Human Resources (HR). This is continuously pursued by Raden Intan State Islamic University of Lampung, which consistently evaluates employee performance and strives to cultivate a positive work culture for all its employees. This study aims to examine the implementation of work culture values among employees within the Postgraduate Program of Raden Intan State Islamic University of Lampung. This research employs a field research design and adopts a descriptive qualitative approach. It utilizes a phenomenological perspective, whereby the researcher seeks to understand the existing reality in order to obtain substantive answers regarding the essence of the work culture phenomenon. The data collection techniques used in this study are: (a) observation, (b) interviews, and (c) documentation. The data analysis technique in this study refers to the framework developed by Miles and Huberman, in which data analysis is carried out through several stages, namely: (1) data reduction, (2) triangulation, (3) data display, and (4) verification or conclusion drawing. The results of this study indicate that the work culture in the Postgraduate environment of UIN functions as a unifying element for the employees. This collective commitment is able to shape personalities with high integrity, which will create Human Resources (HR) that are qualified and excellent. The following are the work culture values that have been developed in the Postgraduate Program of UIN Raden Intan Lampung, namely: (1) Integrity, (2) Professionalism, (3) Innovation, (4) Responsibility, and (5) Exemplary.